In Vitro Transformation of Human Bronchial Epithelial Cells by Diesel Exhaust Particles: Gene Expression Profiling and Early Toxic Responses - Rynning, Iselin (Toxicol Sci, 2018)
Occupational exposure to diesel exhaust may cause lung cancer in humans. Mechanisms include DNA-damage and inflammatory responses. Here, the potential of NIST SRM2975 diesel exhaust particles (DEP) to transform human bronchial epithelial cells (HBEC3) in vitro was investigated. Long-term exposure of HBEC3 to DEP led to increased colony growth in soft agar. Several DEP-transformed cell lines were established and based on the expression of epithelial-to-mesenchymal-transition (EMT) marker genes, one of them (T2-HBEC3) was further characterized. T2-HBEC3 showed a mesenchymal/fibroblast-like morphology, reduced expression of CDH1, and induction of CDH2 and VIM. T2-HBEC3 had reduced migration potential compared with HBEC3 and little invasion capacity. Gene expression profiling showed baseline differences between HBEC3 and T2-HBEC3 linked to lung carcinogenesis. Next, to assess differences in sensitivity to DEP between parental HBEC3 and T2-HBEC3, gene expression profiling was carried out after DEP short-term exposure. Results revealed changes in genes involved in metabolism of xenobiotics and lipids, as well as inflammation. HBEC3 displayed a higher steady state of IL1B gene expression and release of IL-1β compared with T2-HBEC3. HBEC3 and T2-HBEC3 showed similar susceptibility towards DEP-induced genotoxic effects. Liquid-chromatography-tandem-mass-spectrometry was used to measure secretion of eicosanoids. Generally, major prostaglandin species were released in higher concentrations from T2-HBEC3 than from HBEC3 and several analytes were altered after DEP-exposure. In conclusion, long-term exposure to DEP-transformed human bronchial epithelial cells in vitro. Differences between HBEC3 and T2-HBEC3 regarding baseline levels and DEP-induced changes of particularly CYP1A1, IL-1β, PGE(2), and PGF(2α) may have implications for acute inflammation and carcinogenesis.